Profile Analysis of Scientific Literacy Skills in Terms of Competencies, Knowledge, and Attitudes - Yudhistian; Tabitha Sri Hartati Wulandari (Postgraduate, University of Mataram, 2025)
The study aims to describe scientific literacy skills in terms of competencies, knowledge, and attitudes. This is a descriptive quantitative study using a scientific literacy skills questionnaire with three components, using a five-point Likert scale that has undergone validity and reliability testing and has been declared valid and reliable. Data were collected from 165 subjects and analyzed descriptively for interpretation and categorization. The results indicate that scientific literacy skills in terms of competencies fall within the moderate category (74.15%), knowledge in the moderate category (73.97%), and attitudes in the high category (78.22%). The study concludes that the highest level of science literacy is in terms of attitude, while the lowest level is in terms of knowledge. Consequently, the implications for educators are suggested in developing students' science literacy knowledge through learning resources that are integrated with scientific reading materials.